"Curiosity and a Pimp": Exploring Sex Trafficking Victimization in Experiences of Entering Sex Trade Industry Work Among Participants in a Prostitution Diversion Program. Issue 2 (15th March 2017) - Hickle, Kristine; Roe-Sepowitz, Dominique
Abstract : This mixed-methods study explored entry into the sex trade industry and experiences of sex trafficking victimization among 478 adult women enrolled in a prostitution diversion program in a large southwestern state. Written responses to several open-ended survey questions were coded using a template approach to content analysis wherein a priori codes were identified based on characteristics of sex trafficking victimization identified in the Victims of Trafficking and Violence Protection Act of 2000 (U.S. Department of State, 2000 ). Findings revealed that approximately one third of participants ( n  = 161) described sex trafficking experiences on entry into the sex trade industry, and quantitative analysis revealed that women who experienced sex trafficking as part of entering the sex trade industry were more likely to report abuse during childhood and adulthood, to report gang involvement, and to be involved in multiple types of sex trade industry work. Implications for policy and practice are discussed.